MNEMIOPSIS LEIDYI: ШВИДКІСТЬ ЖИВЛЕННЯ РЕБРОПЛАВІВ У МОРІ І ХАРЧОВИЙ ПРЕС ПОПУЛЯЦІЇ НА КОРМОВИЙ ЗООПЛАНКТОН - Фіненко, Г. А.; Романова, З. О.; Аболмасова, Г. І.; Дацик, Н. О.; Аннінський, Б. Є. (Marine Ecological Journal, 2023)
Based on abundance and species composition of M. leidyi food in the sea and experimental data on digestion time the daily ration values of the population in Sevastopol Bay and shelf zone of the Black Sea were estimated. In parallel the seasonal dynamics of abundance, biomass and population structure of M. leidyi and mesozooplankton were studied. These data were the base for the estimation of predatory impact of ctenophore population on zooplankton community in Sevastopol Bay and shelf zone of the Black Sea. Predatory impact of M. leidyi population on forage zooplankton in the coastal zone in a whole in 2008 was rather long in time (June – August) and high (up to 30 % of biomass and 90 % of production per day). As a result forage reserve of planktivorous fish and their food supply were undermined.